Genome-wide DNA methylation of Munro’s microabscess reveals the epigenetic regulation in the pathogenesis of psoriasis - Xu, Xiaoqing; Zhang, Yuxi; Pan, Zhaobing; Zhang, Xiaojing; Liu, Xiaonan; Tang, Lili; Zhang, Xiaoguang; Zhou, Fusheng; Cheng, Hui (Frontiers in Immunology, 2022)
Munro's microabscess is a typical pathological feature in the early psoriatic lesion, mainly characterized by the accumulation of neutrophils in the epidermis. In this genome-wide DNA methylation analysis of psoriatic skin lesions with and without Munro's microabscess, from two batch samples consisting of 114 former samples in the discovery stage and 21 newly-collected samples in the validation stage, we observed 647 overlapping differentially methylated sites (DMSs) that were associated with Munro's microabscess. Subsequently, GO pathway analysis revealed that DNA methylation might affect the physical properties associated with skin cells through focal adhesion and cell-substrate junction and was likely to recruit neutrophils in the epidermis. Via the MEME tool, used to investigate the possible binding transcription factors (TFs) of 20 motifs around the 647 DMSs, it was found that DNA methylation regulated the binding of AP1 family members and the recruitment of neutrophils in the epidermis through the TGF-beta pathway and the TH17 pathway. Meanwhile, combined with our earlier transcriptome data, we found DNA methylation would regulate the expressions of CFDP, SIRT6, SMG6, TRAPPC9, HSD17B7, and KIAA0415, indicating these genes would potentially promote the process of Munro's microabscess. In conclusion, DNA methylation may affect the course of psoriasis by regulating the progression of Munro's microabscess in psoriatic skin lesions.